The juridical nature of the European Court of Justice and the principles of its activity - Vilma Hasneziri (Academicus International Scientific Journal, 2015)

(untitled)
The European Union is a reality closer and closer for Albania as well. The status Albania obtained as a candidate country, not only means a step forward towards the European Union, but it also sets forth a number of challenges to be solved such as, freedom, property, democracy, human rights, the fight against organized crime and corruption etc. Under these circumstances, the analysis of the issues that have to do with the European Union is of a great importance, as in the near future, Albania is designated to join the great European family. The scope of this work is to analyze tow important aspects that have to do with one of the most important institutions of the European Union, such as the European Court of Justice. The first aspect of this work, which is also its first subject, refers to the juridical nature of the European Court of Justice. Analyzing this topic, we shall see that this Court, as per its nature, contains elements of different courts, thus, presenting similarities with the Constitutional Courts of Member States, civil courts, criminal courts, administrative and labour courts and with other international courts as well. However, despite the similarities it presents with other courts, the European Court of Justice is a court of a special kind, “sui generis”, exactly as the European Union is, thus, an organization of a special kind. The second aspect of this paper, which is also its second issue, analyses the fundamental principles where the European Court of Justice bases its activity. The most important principles are that of equality and non discrimination, the principle of protecting and guaranteeing the human rights, the principle of access before the court or the right to address the court, the principle of legality as well as the principles of proportionality and subsidiarity. In this work, especially in the second part, there shall be presented several decisions of the European Court of Justice as well, that have to do with its interpretation on the dispositions of the establishing Treaties as well as the analysis of the above mentioned principles. At the end of this work, there will be given its conclusions as well as the bibliography where it is based on.